Pembuatan Konsep Alat Preparasi Material Cangkang Kapsul Lunak Menggunakan Metode Pahl Dan Beitz - Budi Triyono; Riovano Putranto; Devi Eka Septiyani Arifin (Manutech : Jurnal Teknologi Manufaktur, 2024)
Softgel capsule is a capsule with soft shell texture and is used for fluid or semi-solid medicine substance. Research about softgel capsule in Politeknik Negeri Bandung uses a preparation device to mix the soft capsule shell ingredients. In its operation, this machine has several problems: ineffective method of loading and unloading of materials, unsuitable power for the mixing motor and heating element, and the control system still needs to be improved. Based on these problems, it is neccesary to reverse engineer the preparation device to get better design results so that the device can be operated more effectively. This study consists of three stages: planning, concept generation, and concept evaluation. At the planning stage, data is collected and compiled using the Quality Function Deployment (QFD) method to support the creation of requirement lists. In concept generation stage a design concept was created using the Pahl & Beitz method which was then evaluated using the Pugh weighting method until the final concept was obtained. There are three subfunctions: (1) lifting mechanism, (2) control system, and (3) unloading mechanism. The results of this study are a design concept with rack & pinion lifting mechanism, electrical control system, and sliding valve unloading mechanism.